1983
DOI: 10.1073/pnas.80.20.6361
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous endonuclease-induced DNA fragmentation: an early event in cell-mediated cytolysis.

Abstract: Within minutes of exposure of target cells to cytotoxic T lymphocytes, their nuclear DNA begins to be fragmented. This phenomenon precedes 5"Cr release by at least an hour. DNA fragmentation occurs only when appropriately sensitized cytotoxic T cells are used and is not merely a result of cell death because killing of target cells by heating, freeze/thawing, or lysing with antibody and complement did not yield DNA fragments. Agarose gel electrophoresis of target cell DNA showed discrete multiples of an approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
217
1
4

Year Published

1989
1989
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 530 publications
(232 citation statements)
references
References 22 publications
10
217
1
4
Order By: Relevance
“…Cells treated with PGE1 show high sensitivity with an IC 50 of 0.2 mM (Figure 1c). PGE 1 also causes DNA fragmentation (Figure 1d lower panel) typical of apoptosis as described in other cells (Duke et al, 1983;McConkey et al, 1990).…”
Section: Prostaglandin Treatment Induces Apoptosis Of Ipc-81 Cellssupporting
confidence: 66%
“…Cells treated with PGE1 show high sensitivity with an IC 50 of 0.2 mM (Figure 1c). PGE 1 also causes DNA fragmentation (Figure 1d lower panel) typical of apoptosis as described in other cells (Duke et al, 1983;McConkey et al, 1990).…”
Section: Prostaglandin Treatment Induces Apoptosis Of Ipc-81 Cellssupporting
confidence: 66%
“…The morphological changes associated with ATP-induced apoptosis are blocked in thymocytes by the inhibitors of macromolecular assembly, cycloheximide and actinomycin D. Likewise, ATP-mediated DNA fragmentation in EL4 cells is suppressed by inhibitors of transcription as well as by zinc, an endonuclease inhibitor (6,8,10). The extent of fragmentation is not directly proportional to the ATP concentration, however, as the fragmentation decreases when the ATP concentration is increased beyond 0.5 mM.…”
Section: Discussionmentioning
confidence: 88%
“…In the 1980s the field was divided by two opposing hypotheses, one advocating colloid osmotic lysis as a result of pore formation in the target cell similar to complementmediated lysis [73], and the other supporting active induction of programmed cell death, the concept of which was just making its debut in the world of immunology. The first concrete evidence for killing by apoptosis rather than passive osmotic lysis came from a study that observed rapid DNA fragmentation by an endogenous endonuclease after exposure of target cells to CTL [74]. Earlier studies using electron microscopy had described extensive nuclear changes and surface blebbing in target cells, results that had, in retrospect, hinted at apoptosis [75].…”
Section: Cell-mediated Cytotoxicitymentioning
confidence: 99%